Quantitative study of the effect of L-dopa and phenoxybenzamine on the rigidity of Parkinson's disease. Issue 3 (June 1973) - Andrews, Colin J.; Burke, David
Abstract : The static and dynamic components of the tonic stretch reflex and shortening reactions have been studied in biceps brachii, triceps, hamstrings, and quadriceps muscles of 19 patients with Parkinson's disease before and during L -dopa therapy. Clinical improvement during L -dopa administration correlated with a reduction in the dynamic component of the tonic stretch reflex in biceps, triceps, and quadriceps but not the hamstrings muscle, and with the static component of the tonic stretch reflex in biceps and triceps but not quadriceps and hamstrings muscles. The only shortening reaction consistently reduced during the L -dopa treatment period was the dynamic shortening reaction of the triceps muscle. The responses of the stretch reflexes to changes in muscle length were not altered by L -dopa therapy. In severely disabled patients the hamstrings and quadriceps stretch reflexes were maximal in a position of partial flexion of the knee joint and this response to muscle length was not altered in these patients despite a dramatic lessening of rigidity in some patients. Shortening reactions commonly remained in some patients after the stretch reflex of the antagonistic muscle was abolished by L -dopa therapy. The administration of phenoxybenzamine to patients being treated with L -dopa reduced the different components of rigidity more than L -dopa alone, and the responses were consistent with phenoxybenzamine suppressing predominantly the descending noradrenergic pathway.